Effect of nintedanib on lung function in patients with systemic sclerosis-associated interstitial lung disease: further analyses of a randomized, double-blind, placebo-controlled trial - Maher, Toby M.; Mayes, Maureen D.; Kreuter, Michael; Volkmann, Elizabeth R.; Aringer, Martin; Castellvi, Ivan; Cutolo, Maurizio; Stock, Christian; Schoof, Nils; Alves, Margarida; Raghu, Ganesh (Arthritis & rheumatology, 2021)
Objective In the SENSCIS trial in subjects with systemic sclerosis-associated interstitial lung disease (SSc-ILD), nintedanib reduced the rate of decline in forced vital capacity (FVC) over 52 weeks by 44% versus placebo. This study was undertaken to investigate the effects of nintedanib on categorical changes in FVC and other measures of ILD progression. Methods In post hoc analyses, we assessed the proportions of subjects with categorical changes in FVC % predicted at week 52 and the time to absolute decline in FVC of ≥5% predicted or death and absolute decline in FVC of ≥10% predicted or death. Results A total of 288 subjects received nintedanib and 288 subjects received placebo. At week 52, in subjects treated with nintedanib and placebo, respectively, 55.7% and 66.3% had any decline in FVC % predicted, 13.6% and 20.1% had a decline in FVC of >5% to ≤10% predicted, and 3.5% and 5.2% had a decline in FVC of >10% to ≤15% predicted; 34.5% and 43.8% had a decrease in FVC of ≥3.3% predicted (proposed minimal clinically important difference [MCID] for worsening of FVC), while 23.0% and 14.9% had an increase in FVC of ≥3.0% predicted (proposed MCID for improvement in FVC). Over 52 weeks, the hazard ratio (HR) for an absolute decline in FVC of ≥5% predicted or death with nintedanib versus placebo was 0.83 (95% confidence interval [95% CI] 0.66−1.06) (P = 0.14), and the HR for an absolute decline in FVC of ≥10% predicted was 0.64 (95% CI 0.43−0.95) (P = 0.029). Conclusion These results suggest that nintedanib has a clinically relevant benefit on the progression of SSc-ILD.